Transformative Roles of NGOs in Advancing Indigenous Social Justice through Participatory and Culturally Embedded Strategies in Indonesia - Amelia, Anita Reski; Arief, Siti Hardiyanti; Hasan, Kurnia (Journal Social Humanity Perspective, 2024)
This is a qualitative study that examines the role played by non-governmental organizations (NGOs) in the quest of social justice among the indigenous people in Indonesia. Through interviewing the NGO practitioners and indigenous leaders in different regions, the research establishes some of the most vital roles such as legal advocacy role, cultural preservation role, and taking the indigenous views to the making of a public policy. The discussions reiterate that sustainability requires long-term, culturally respectful partnerships as well as absolute opposition against donor-induced and short-term cycle of projects. As far as the managerial analysis is concerned, the work criticizes traditional models of operationalizing NGOs and proposes more relational, participatory and adaptive frameworks. Instead, NGOs are perfectly placed as an agent of indigenous agency and self-determination so that they do not merely operate externally as outsiders. In its turn, the study will contribute to the field of non-profit management research since it describes social justice as a continuous, contextual process instead of seeking it out as a quantitative result. It also provides pragmatic information to the practitioners as well as to the scholars who are interested in redefining the NGO practice to respond to the community-determined objectives and justice systems.